Comparative analysis of influenza A(H3N2) virus hemagglutinin specific IgG subclass and IgA responses in children and adults after influenza vaccination - Manenti, Alessandro; Tete, Sarah M.; Mohn, Kristin G.-I.; Jul-Larsen, Åsne; Gianchecchi, Elena; Montomoli, Emanuele; Brokstad, Karl A.; Cox, Rebecca J. (Vaccine, 2017)
•LAIV3 induced age-related hemagglutination inhibition antibody responses.•IgG1 was the main IgG subclass detected followed by IgG3.•Significant hemagglutinin-specific IgG1 and IgA1 response in children but not adults.•LAIV3 and IIV3 induced IgG antibodies with comparable and significantly increased avidity. Two different influenza vaccines are generally used in many countries; trivalent live attenuated influenza vaccine (LAIV3) and trivalent inactivated influenza vaccine (IIV3). Studies comparing the antibody response to IIV3 and LAIV3 commonly investigate the seroprotective response by hemagglutination-inhibition (HI) assay. However, there is limited data regarding comparative analysis of IgG subclass and IgA responses induced by LAIV3 and IIV3. Fifteen children <5years received 2 doses of LAIV3 while 14 children aged 10–17years received one dose. In addition, 15 adults were vaccinated with either intranasal LAIV3 or intramuscular IIV3. We analyzed the H3N2 humoral responses by HI assay and the hemagglutinin (HA) specific IgG1, IgG2, IgG3, IgG4 and IgA1 responses by ELISA. Furthermore, we investigated the avidity of induced IgG antibodies. Pre-existing seroprotective HI antibodies were present in adults (73%) previously vaccinated with IIV3. Vaccination resulted in a significant increase in HI titers in all groups, except LAIV3 vaccinated adults. Furthermore, a negative correlation between age and HI titers in LAIV3 vaccinated subjects was observed post-vaccination. LAIV3 in children and IIV3 in adults induced HA-specific IgG1, low IgG3 but no IgG2 or IgG4. Moreover, significant IgA1 responses were only induced in children. Interestingly, IIV3 and LAIV3 induced IgG antibodies with comparable and significantly augmented avidity post-vaccination in children and adults. Our results suggest that age and/or exposure history play a significant role in determining the antibody response. Clinical trial registry: ClinicalTrials.gov NCT01003288 and NCT01866540